Evaluation of Sports Class Program Management SMP Negeri 1 Sumber Kabupaten Cirebon - SUKAWI, SUKAWI; Soegiyanto, Soegiyanto; Pramono, Harry (Journal of Physical Education and Sports, 2020)
This study aims to analyze and evaluate the planning system, the organizing system, the actuating system, and the controlling system. This research uses a qualitative approach. Data collection techniques were observation, interviews, and documentation. The data sources were taken from school principal, sports class coordinator, coaches, athletes, and parents. Data analysis techniques used data triangulation with data reduction, data presentation, and drawing conclusions. The results of this study: (1) The planning system for sports class program management has met the categorization criteria, i.e. it is clear who, what, when, where, and how it is done; (2) Organizing management of the sports class program meets the categorization criteria, i.e. complete management, a work mechanism, unclear written job description, routine activities, and talks at the beginning of the year; (3) Actuating of sports class program management has met the categorization criteria, i.e. implementation, achievements, carrying out activities, and completing the 5M (man, money, method, material, mechine); 4) Controlling management of the sports class program meets the categorization criteria, i.e. supervision, report, evaluation, and monitoring. Conclusions: (1) Planning management is very good; (2) Organizing the management is good; (3) Actuating the management is very good; (4) Controlling management is very good.